Use of text and GV/GO study as Radioactivity teaching strategies (Research, Society and Development, 2019)
Several pedagogical trends have gained prominence in the school environment, especially the teaching strategies, which aim at an effective methodology for students in the realization of varied mental constructions in the learning process. The objective of this study is to evaluate the applicability of the "Text Study" and "GV/GO" strategies in the classroom based on the topic Radioactivity, taking into account the teaching approaches discussed in a master's degree and thus generate reflections on teaching and learning practices. This study is a qualitative field research applied with master's degrees in science and mathematics education, where it was intended to collect descriptive information through recording of the participants' speeches. It was noticed that the use of the "Text Study" and "GV/GO" teaching techniques served as a basis for the understanding and reflection of the presented content, making possible the use of these techniques by the different areas of knowledge (Mathematics, Biology, Physics and Chemistry) according to the area of the participants of this research.